2012
DOI: 10.1038/nature10758
|View full text |Cite|
|
Sign up to set email alerts
|

Exercise-induced BCL2-regulated autophagy is required for muscle glucose homeostasis

Abstract: Exercise has beneficial effects on human health, including protection against metabolic disorders such as diabetes1. However, the cellular mechanisms underlying these effects are incompletely understood. The lysosomal degradation pathway, autophagy, is an intracellular recycling system that functions during basal conditions in organelle and protein quality control2. During stress, increased levels of autophagy permit cells to adapt to changing nutritional and energy demands through protein catabolism3. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

52
967
9
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,007 publications
(1,032 citation statements)
references
References 31 publications
(40 reference statements)
52
967
9
4
Order By: Relevance
“…Our data show that aerobic exercise induces a reduction in p62/SQSTM1, suggesting an increase in the expression of autophagy regulatory proteins after the training program. These results are in line with previous studies which showed an increase in LC3II and a decrease in p62/SQSTM1 expression after exercise in different rodent (He et al 2012;Lira et al 2013;Bayod et al 2014) and human models (Schwalm et al 2015), hence supporting the notion that high-intensity exercise induces an increased autophagy.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our data show that aerobic exercise induces a reduction in p62/SQSTM1, suggesting an increase in the expression of autophagy regulatory proteins after the training program. These results are in line with previous studies which showed an increase in LC3II and a decrease in p62/SQSTM1 expression after exercise in different rodent (He et al 2012;Lira et al 2013;Bayod et al 2014) and human models (Schwalm et al 2015), hence supporting the notion that high-intensity exercise induces an increased autophagy.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, both acute and chronic endurance exercise seem to induce adaptations in the autophagy pathway Jamart et al 2012;Schwalm et al 2015;Weng et al 2013). However, it should be noted that most of the available data related to the effects of exercise on autophagy proteins in different tissues have been obtained from rodent studies, where long training periods induce a significant increase in the protein expression of beclin-1 and LC3I/II associated to a lowered expression of p62/SQSTM1 in muscles (He et al 2012;Kim et al 2013;Lira et al 2013; (Bayod et al 2014). Nevertheless and as far as we know, few investigations have studied the effects of exercise on the age-related impairment of autophagy using a murine model.…”
Section: Discussionmentioning
confidence: 99%
“…Detailed metabolic analysis revealed that Atg7 ablation causes a failure to mobilize serum-free fatty acids and initiates the rapid depletion of liver glycogen stores, resulting in low serum glucose levels and impaired metabolic fitness in starved animals 95 . Moreover, during exercise, autophagy is induced in cardiac and skeletal muscles, adipose tissue and pancreatic β-cells, which provides protection against glucose intolerance 101 . Similarly, in pancreatic β-cells, autophagy is important for maintaining glucose tolerance because mice lacking ATG7 in β-cells have reduced serum insulin levels and hyperglycaemia 102,103 .…”
Section: Phagophore Autolysosomementioning
confidence: 99%
“…Indeed, exercise has been proven beneficial in the treatment of neuro degenerative diseases associated with misfolded pro teins 169 . Interestingly, exercise induces autophagy in cardiac muscle of mice 170 . In addition, voluntary exercise in a mouse model of desmin related cardiomyopathy reduced protein aggregation and disease progression 171 .…”
Section: Calorific Restriction and Exercisementioning
confidence: 99%